Cumulative Growth in User-Generated Content Production: Evidence from Wikipedia - Aaltonen, Aleksi; Seiler, Stephan (Management Science, 2016)
Open content production platforms typically allow users to gradually create content and react to previous contributions. Using detailed edit-level data across a large number of Wikipedia articles, we investigate how past edits shape current editing activity. We find that cumulative past contributions, embodied by the current article length, lead to significantly more editing activity, while controlling for a host of factors such as popularity of the topic and platform-level growth trends. The magnitude of the effect is large; content growth over an eight-year period would have been 45% lower in its absence. Our findings suggest that other open content production environments are likely to also benefit from similar cumulative growth effects. In the presence of such effects, managerial interventions that increase content are amplified because they trigger further contributions. Data, as supplemental material, are available at http://dx.doi.org/10.1287/mnsc.2015.2253 . This paper was accepted by Pradeep Chintagunta, marketing.